ANALISIS TEKNIK ANGKAT BESI ATLET PABBSI KABUPATEN MUSI RAWAS - Ramadhan Wahyu Jatmiko; Wawan Syafutra; Hengky Remora (Jurnal Binagogik, 2024)
This study aims to describe the weightlifting techniques of PABBSI athletes in Musi Rawas Regency. This research is a type of qualitative descriptive research. The subjects of this research were PABBSI coaches and athletes in Musi Rawas Regency. Data collection techniques were carried out using interviews, observation and documentation. Data were analyzed using components recommended by Miles and Huberman. Data collection was carried out in the afternoon after the collected data was immediately analyzed. The research results showed that the value of movement in weightlifting techniques was visible when the researchers made observations. The research on weightlifting techniques illustrates that the total number of 4 athletes who were observed one by one were said to be able to perform snatch and clean and jerk weightlifting techniques correctly and appropriately. The results of this research show that the movements in the snatch and clean and jerk weightlifting techniques are categorized as good.